A Semiotic Analysis of War Life Representation in the Event of World War I: Operation Alberich on Cinematographical Elements of One-Shot Technique in Sam Mendes’ 1917 (2019) - Atinia Hidayah; Anggi Laksamana Putra (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2022)
This research is conducted to analyze the cinematographical elements revealed in Sam Mendes' 1917 (2019) movie and the war life in the World War I represented in 1917 (2019). There are two problem statements that the researcher used in this research, first, how do cinematographical elements in One-Shot Technique present war life?? Second, how is war life reflected in the Sam Mendes’ 1917 (2019)?? The researcher used the qualitative method to examine the problem. The theory and approaches that the researcher used is Cinematographical Elements and Semiotic. This study also includes the procedures of collecting data and procedure of analyzing data. The result of this study, first, Cinematographical Elements provide signs of war life, second, Semiotic explained about the war life of soldiers and civilians in Operation Alberich in the era of World War I.